Anticancer effect of hypophyllanthin, niranthin and lintetralin from phyllanthus amarus on HeLa cells and NIH/3T3 cells. - Mohd Azlan Nafiah (Tanjong Malim, 2019)
Anticancer effect of hypophyllanthin, niranthin and lintetralin from phyllanthus amarus on HeLa cells and NIH/3T3 cells. by Mohd Azlan Nafiah